The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms - Deschodt, Christian M.; Davis, Adrian L.v.; Daniel, Gimo M. (Zootaxa, 2019)
Five new species of Epirinus Dejean, 1833 were discovered during databasing of dung beetle collections. These are described here, as Epirinus inparrugosus Deschodt & Davis, new species, Epirinus jacobsae Deschodt & Davis, new species, Epirinus muellerae Deschodt & Davis, new species, Epirinus pseudorelictus Deschodt & Davis, new species and Epirinus schoolmeestersi Deschodt & Davis, new species. Using comparisons based on morphology, we also studied the taxonomic status of five morphologically-allied, allopatric populations of Epirinus from isolated forest patches in northeast KwaZulu-Natal, South Africa, and eastern eSwatini (formerly Swaziland). On the basis of these comparisons we synonymize Epirinus hluhluwensis Medina & Scholtz, 2005, and Epirinus ngomae Medina & Scholtz, 2005, with Epirinus davisi Scholtz & Howden, 1987. A distribution map is provided for all of these species. Furthermore, the first record for the genus in Namibia is reported and an updated key is provided for all known species of the genus.